SCIENTIFIC AND METHODOLOGICAL ASPECTS OF ASSESSING THE SUSTAINABLE DEVELOPMENT OF RURAL AREAS AND COMMUNITIES - TYMOSHENKO, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article reveals the scientific and methodological principles of assessing the current state of rural areas and community development in Ukraine under the conditions of expanding the local self-government powers. It is proved that in accordance with the global trends of modern socio-ecological and economic development, the development of new theoretical and methodological approaches to the organization of rural territories, assessment of their development level, identification of urgent problems in the formation and use of rural territorial communities’ budgets is of great importance.The essence of sustainable rural development was studied, and the determinants of its formation were summarized. It was established that the model of sustainable development of rural areas and communities includes social, economic, ecological, cultural and educational spheres. At the same time, the economic component is based on obtaining the maximum aggregate income while preserving and multiplying the functioning aggregate capital and income of competitive territorial communities, increasing the volume of production of agricultural products. Social component is based on creating optimal social conditions and improving the life quality of the rural population. Ecological one is based on the balanced coherence of biological and natural ecosystems. Cultural and educational component is based on the formation of national culture and ideology, which would cultivate respect for a healthy rural way of life in the countryside.Having studied the existing methodical approaches to assessing the state of development of rural areas and communities, it has been proven that the algorithm for conducting an analytical study should consist of three stages: preparatory, analytical and calculation, and final. It is substantiated that without constant development and improvement of scientific and methodological tools, it is impossible to assess the acuteness of the existing problems of rural development and to develop strategic directions for their solution.
Keywords: rural territories; rural development; territorial communities; administrative-territorial reform; financial capacity; assessment; diagnostics